(untitled) (مجلة العلوم الاقتصادية والسياسية, 2016)
his paper develops and tests a panel cointegration model to examine the interaction between economic growth and its determinants of selected North African Countries. The analysis is applied to five heavily indebted North African countries-namely Algeria, Egypt, Mauritania, Morocco, and Tunisia. The results based on Pedroni cointegratioan and fully Modified OLS (FMOLS). The tests proposed by Pedroni suggest that servicing a heavy debt could have an adverse impact on economic growth and capital inflow which in turn worsens the debt problem.